1976
DOI: 10.1128/aac.9.5.810
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Plasmids of Pseudomonas aeruginosa: Change from Conjugative to Nonconjugative in a Hospital Population

Abstract: Properties ofa population ofcarbenicillin-and gentamicin-resistant, tobramycin-susceptible Pseudomonas aeruginosa at Veteran's Administration Hospital, Cincinnati, Ohio, have been followed during a 16-month period. As originally described, the strains were isolated from patients with urinary tract colonizations and were predominantly Parke-Davis immunotype 7. For the majority of these organisms, antibiotic resistance was correlated with the presence of a selfconjugative plasmid of incompatibility group P-2. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…4. The fragments of each of the plasmids of transconjugants 2 through 7 of each appear to form 13 (12,17).…”
Section: Methodsmentioning
confidence: 99%
“…4. The fragments of each of the plasmids of transconjugants 2 through 7 of each appear to form 13 (12,17).…”
Section: Methodsmentioning
confidence: 99%
“…Resistance transfer studies showed that antibiotic resistance in Pseudomonas from this hospital continues to be due to nonconjugative plasmids (11). Studies on a more limited number of other'gram-negative bacilli showed the presence of conjugative plasmids.…”
Section: Methodsmentioning
confidence: 99%
“…Four facultative organisms tested included two Enterobacter cloacae and two Serratia marcescens, all with antibiogram Tcr, Gr, Tr, Cbr. Each strain was tested for single transfer of its Smr, Tcr, Gr, and T' markers in parallel platings using P. aeruginosa PL1 (11) For other gram-negative bacilli, the monthly rate of isolation of Gr and T organisms varied from 1.7 to 9.8% and from 1.7 to 8.1%, respectively (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gentamicin has been useful in treating such infections, but several outbreaks of plasmid-mediated gentamicin resistance (Gm) in Klebsiella, Serratia, and Pseudomonas strains (16,19,22,28,33,36) point to its lessened usefulness. Resistance to gentamicin and other clinically useful antibiotics, including ampicillin and carbenicillin, has also been widely disseminated through transposons (14,25,28,30).…”
mentioning
confidence: 99%